Developmental and Cellular Basis of Vertical Bar Color Patterns in the East African Cichlid Fish Haplochromis latifasciatus - Liang, Yipeng; Gerwin, Jan; Meyer, Axel; Kratochwil, Claudius F. (Frontiers in Cell and Developmental Biology, 2020)
The East African adaptive radiations of cichlid fishes are renowned for their beautiful diversity in coloration. Yet, the developmental basis of pigment pattern formation remains largely unknown. One of the most common melanic patterns in cichlid fishes are vertical bar patterns. Here we describe the ontogeny of this conspicuous pattern in the Lake Victoria species Haplochromis latifasciatus. Beginning with the larval stages we tracked the formation of this stereotypic color pattern and discovered that its macroscopic appearance is largely explained by an increase in melanophore density and accumulation of melanin during the first three weeks post fertilization. The embryonal analysis is complemented with cytological quantifications of pigment cells in adult scales and the dermis beneath the scales. In adults, melanic bars are characterized by a two to three-fold higher density of melanophores than in the intervening yellow interbars. We found no strong support for differences in other pigment cell types such as xanthophores. Quantitative PCRs for twelve known pigmentation genes showed that expression of melanin synthesis genes tyr and tyrp1a is increased five to six-fold in melanic bars, while xanthophore and iridophore marker genes are not differentially expressed. In summary, we provide novel insights on how vertical bars, one of the most widespread vertebrate color patterns, are formed through dynamic control of melanophore density, melanin synthesis and melanosome dispersal.